Determinan Kinerja Keuangan Yang Ditinjau Dari Good Corporate Governance, Leverage dan Ukuran Perusahaan (Sub. Sector Perusahaan BUMN yang Terdaftar Di BEI tahun 2013-2018) - Lola Dwi Antikasari; Rosa Nikmatul Fajri; Riana R Dewi (Owner : Riset dan Jurnal Akuntansi, 2020)
Financial performance as a benchmark for the success of the company's work in a certain period. Financial performance is also used as a basis for determining the company's strategy in the future. The purpose of this study is to analyze the effect of good corporate governance (board size), leverage (DER) and company size on financial performance (ROA). This study uses a population of 120 data from SOE companies listed on the Indonesia Stock Exchange in 2013-2018. And produced a sample of 78 company data. The sampling technique uses purposive sampling. The research instrument in the form of documentation (taking company financial statements). Data analysis method used is multiple linear regression method. The results showed that the size of the board of directors had a positive effect on financial performance. The leverage variable has a negative effect on financial performance. While the size of the company has no effect on financial performance. The benefits of this study are as a reference for further research. Besides that, it can be used as a management guideline in analyzing the company's financial performance.